2013
DOI: 10.1111/febs.12374
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a sphingolipid‐specific phospholipase D activity associated with the generation of phytoceramide‐1‐phosphate in cabbage leaves

Abstract: The structure and biosynthetic route for an unidentified lipid (lipid X) detected by TLC of cabbage (Brassica oleracea) lipids was determined. Lipid X is a phospholipid that is resistant to mild alkali and detectable by MALDI-TOF MS as an adduct with Phos-tag, a phosphate-capture zinc complex. Various α-hydroxy fatty acids (16:0, 22:0, 24:0 and 24:1) were detected by GC-MS of fatty acid methyl esters prepared from lipid X. The deacyl derivative of lipid X was determined to be 4-hydroxysphingenine (dehydrophyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 40 publications
8
22
1
Order By: Relevance
“…Although it has been reported that Brassicacea extracts (from cabbage and Arabidopsis) have GIPC-specific phosphatase activity (Tanaka et al, 2013), as yet the gene encoding the enzyme responsible has not been cloned. Identification of this enzyme will be very beneficial for GIPC research, enabling NMR characterization of the released glycan.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that Brassicacea extracts (from cabbage and Arabidopsis) have GIPC-specific phosphatase activity (Tanaka et al, 2013), as yet the gene encoding the enzyme responsible has not been cloned. Identification of this enzyme will be very beneficial for GIPC research, enabling NMR characterization of the released glycan.…”
Section: Discussionmentioning
confidence: 99%
“…Nipponbare, was cultivated on soil at 28°C under 12 h dark/12 h light cycles. To inactivate potent sphingolipid‐degrading enzymes present in plant tissues (Tanaka et al ., ), harvested tissues (100–300 mg) were immediately immersed in isopropanol prewarmed at 80°C and kept for 10 min to inactivate lipid‐degrading enzymes, followed by storage at −30°C until use. Seeds obtained from heterologous lines of oni mutants were germinated and grown in tapwater under the same conditions.…”
Section: Methodsmentioning
confidence: 99%
“…29 Finally, a phospholipase D activity that specifically hydrolyzes GIPCs and produces phytoceramide-1-phosphate (PC1P) have been recently identified in Brassicaceae. 30 Authors suggested that GIPC-PLD may play an important signaling role in the biological response in plant cells by producing signaling molecules, but the mechanism of regulation of the enzyme activity is largely unknown. GIPC-PLD could also play a role in de-anchoring GPIC-anchored proteins, see above.…”
Section: Gipc Precursors Of Signaling Moleculesmentioning
confidence: 99%